2008
DOI: 10.1017/s0030605308000161
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring population decline: can transect surveys detect the impact of the Ebola virus on apes?

Abstract: In 2004 the Ebola virus caused a drastic decline in western gorilla Gorilla gorilla abundance at Lokoué Bai, a clearing in Odzala National Park, Republic of Congo. This decline was detected by observations of gorillas visiting the clearing. We confirm that the sympatric chimpanzee Pan troglodytes population was also affected by the Ebola outbreak, and test whether the decline in the ape population would have been detected with linetransect surveys, the most commonly used wildlife monitoring methodology in Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…From our best fitted model (Model 2), there was no evidence of a significant direct correlation between the probability of nest decay and "topography". The latter is a potentially overlooked variable which may influence tree cover and thus the availability of plants used for nesting and should be considered in future studies (Devos et al 2008). Rainfall had an effect on the mean nest decay rate in the MDNP, increasing the probability of nest decay in the first month of the nest's existence.…”
Section: Discussionmentioning
confidence: 97%
“…From our best fitted model (Model 2), there was no evidence of a significant direct correlation between the probability of nest decay and "topography". The latter is a potentially overlooked variable which may influence tree cover and thus the availability of plants used for nesting and should be considered in future studies (Devos et al 2008). Rainfall had an effect on the mean nest decay rate in the MDNP, increasing the probability of nest decay in the first month of the nest's existence.…”
Section: Discussionmentioning
confidence: 97%
“…Linear Transect Surveys are the most widely used methods to estimate mammal densities [Chiarello, 2000; Devos et al, 2008b; Drummer & McDonald, 1987; Plumptre, 2000; Plumptre & Reynolds, 1996; Wanyama et al, 2010]. These methods assume that there is a detection probability that depends exclusively on the perpendicular distance from the trail to the nest [Buckland et al, 2001].…”
Section: Methodsmentioning
confidence: 99%
“…This value takes into account the reuse of old nests by chimpanzees, a behavior that we documented in our study site (we regularly observed old degraded nests with fresh leaves at the top). The methodological limitations of the standing crop nest count method have been subject to numerous studies (Blom et al 2001;Devos et al 2008;Hashimoto 1995;Plumptre and Reynolds 1996;Tutin et al 1995;Walsh and White, 2005). The formula developed by Ghiglieri (1984) to estimate ape density is based on the density of individual nests and rests on the assumption that nests are placed randomly throughout the study area.…”
Section: Data Collection and Analysismentioning
confidence: 99%